Modelagem do crescimento e da produção em classes de diâmetro para plantios de Pinus taeda L. não desbastados - Viana, Josmar de Jesus (2016)
This study aimed to compare the method of prediction and recovery of Weibull function parameters in modeling the growth and production in diameter classes for Pinus taeda L., in the region of Telêmaco Borba, Parana state. The data used in the adjustment of the models have their origin in permanent plots of settlements located in the municipality of Telêmaco Borba, State of Parana. Models were fitted to hypsometric models and thinning. It was used projection models to generate the settlement of the attributes required for adjusting the parameters of the Weibull 3P probability density function, two systems, one using the Parameter Recovery Method (PRM) by the method of moments, and the other by the Parameters Prediction Method (PPM) using implicit equations. The frequencies evaluated were designed using the adhesion test Kolmogorov-Smirnov (K-S). The wood assortment is designed and submitted to the identity test of models Leite and Oliveira (L & O). The attributes projection models produced consistent and accurate projections. The Parameter Recovery Method (PRM) used for projection of the Weibull function coefficient was superior to the Parameters Prediction Method (PPM) by the K-S test. For the test L & O the relative output per hectare and assortments, the Parameter recovery Method (PRM) was also higher to generate the necessary projections.